For a Roof Over One’s Head: Socially Distanced Section and Access to Housing and Amenities in India. - Mahadeva, M. (2007)
Government interventions in India have though checked the incidence of housing shortage to some extent yet these efforts have not been successful in providing housing benefits to almost half of the socially distanced households belonging to Scheduled Castes. The country, owing to distortions in its policy, is facing housing problem of huge magnitude, both quantitatively and qualitatively. The position of the housing amenities is also not different. Unfortunately, the distance between housing development and the requirements of the Scheduled Castes has been widening, and this has emerged as a major problem for the country. This paper is an attempt to consider the problem from its source, in its totality to facilitate formulation of alternative policy options in the country.